Catalysis of dinitrogen activation and reduction by a single Fe13 cluster and its doped systems. Issue 2 (15th December 2022) - Cheng, Ran; Cui, Chaonan; Luo, Zhixun
Abstract : The catalysis of dinitrogen activation and reduction by a single cluster Fe13 and its doped systems is studied, shedding light on the advantages of Fe12 Nb as an ideal candidate. Abstract : Catalyzing N2 reduction to ammonia under ambient conditions is known to be significant both in the fertilizer industry and life sciences. To unveil the synergy of multiple sites, here, we have studied the catalysis of ammonia synthesis using a typical Fe13 cluster and its doped systems, Fe12 X (X = V, Cr, Mn, Co, Ni, Cu, Zn, Nb, Mo, Ru, and Rh). The energetics analysis showed that center substitution (X@Fe12 ) was favored while doping single V, Cr, Co, and Mo atoms, whereas Mn, Ni, Cu, Zn, Nb, Ru, and Rh tended to form shell-doped structures (Fe12 X). Among all the 13 clusters, Fe12 Nb exhibited the lowest activation energy for N2 dissociation; moreover, in the hydrogenation process, Fe12 Nb could convert N2 to ammonia efficiently. We have fully illustrated the reaction dynamics and structural chemistry essence of these diverse 13-atom systems and propose Fe12 Nb as an ideal candidate for catalytic ammonia synthesis.